Oil palm trunk and its utilization / Muhamad Azuan Muhamad Yasir - Muhamad Yasir, Muhamad Azuan (2007)
Oil palm (Elaeis quineensis Jacq.) has now become one of the major raw materials for wood industry. This material look have a big potential to substituted raw material for wood industry. Oil palm has continuous material where Malaysia expected to replanted 5.10 million hectares oil palm until 2020. Besides that, research of properties of oil palm trunk was studied to know that raw material is suitable as a new material for wood industry. This research is important to make it raw material as an alternative materials not only for wood industry but also for other related industries.